Inovasi Produk Halal UMKM dalam Perspektif Manajemen Bisnis Syariah - Rosa Da’mai (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
The halal industry has experienced significant growth, encouraging Micro, Small, and Medium Enterprises (MSMEs) to continuously innovate in order to compete globally. This study aims to examine the strategies of halal product innovation implemented by MSMEs from the perspective of islamic business management, identify the key driving factors behind innovation in the global market, and analyze its influence on Muslim consumers preferences. This research adopts a literature review methode using various scholarly journals and academic sources. The findings show that effective innovation strategies include collaboration between the government and industry, improvement of ptoduct quality and halal certification, digital technology utilization, and marketing approaches aligned with Islamic pronciples. The main drivees of innovation consist of product and process development, technology and digitalization, the high consumption value of halal products among indonesian consumers a, comprehensive legal framework, import substitution policies, and stakeholder synergy. Halal product innovation has proven to positively influence Muslim consumers preferences, particularly in terms of trust, loyalty, and perceived value. This study highlights that Islamic business management, which emphasizes blessing, ethicts, and sustainability, plays a crucial role in strengthening the global competitiveness of halal MSMEs.